Optimizing access and configuration of trauma centre care in New South Wales. Issue 5 (May 2019) - Gomez, David; Larsen, Kristian; Burns, Brian J.; Dinh, Michael; Hsu, Jeremy
Highlights: The New South Wales trauma system has above average potential access to trauma centre care, challenges remain in rural areas. Redistribution of the number of urban TCs in NSW could be achieved without a significant impact on potential access to care. Our approach can be utilized as an initial tool to evaluate a trauma system where overabundance of coverage is present. Abstract: Introduction: Getting the right patient, to the right place, at the right time is dependent on a multitude of modifiable and non-modifiable factors. One potentially modifiable factor is the number and location of trauma centres (TC). Overabundance of TC dilutes volumes and could be associated with worse outcomes. We describe a methodology that evaluates trauma system reconfiguration without reductions in potential access to care. We used the mature trauma system of New South Wales (NSW) as a model given the perceived overabundance of urban major trauma centres (MTC). Methods: We first evaluated potential access to TC care via ground and air transport through the use of geographic information systems (GIS) network analysis. Potential access was defined as the proportion of the population living within 60-min transport time from a potential scene of injury to a TC by ground or rotary-wing aircraft. Sensitivity analyses were carried out in order to account for potential pre-hospital interventions and/or transport delays; travel times of 15-, 30-, 45-, 60-, and 90-min were also analyzed. We then evaluated if the current configuration of the system (number of urban MTS in the Sydney basin) could be optimized without reductions in potential access to care using two GIS methodologies: location-allocation and individual removal of MTC. Results: 86% of the NSW population has potential access to a TC within 60 min ground travel time; potential access improves to 99% with rotary-wing transport. The 1% of the population without potential TC access lives in 48% of the land area (>384, 000km2). Utilizing two different methodologies we identified that there was no change in potential access by ground transport after removing 1 or 2 MTC in the Sydney basin at the 30-, 45-, and 60-min transport times. However, 0.02% and 0.5% of the population would not have potential access to MTC care at 15 min after removing one and two MTC respectively. Discussion: Redistribution of the number of MTC in the Sydney basin could be achieved without a significant impact on potential access to care. Our approach can be utilized as an initial tool to evaluate a trauma system where overabundance of coverage is present.